PENGARUH PENDIDIKAN KARAKTER TERHADAP HASIL BELAJAR SISWA PADA TEMA INDAHNYA KEBERSAMAAN - Marnawati Sitorus; Rumiris Lumban Gaol; Antonius Remigius Abi; Darinda Sofia Tanjung (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2020)
This study aimed to determine the effect of character education on students’ learning outcomes on the theme of “Indahnya Kebersamaan" at grade IV SD Negeri 177072 Halado in the academic year 2020/2021. The population of this study was all students of SD Negeri 177072 totaling 295 students. The samples were selected by purposive sampling; in this case, the researcher chose grade IV consisting of 40 students as the samples. A quantitative method, that was a type of survey method was utilized in this study. Then, the hypotheses were examined by t test. The results of this study indicated that the average score of character education was 63.875, which was included in High category, and the score of learning outcomes was 67.24, which was also included in High category. This was supported by the result of t test in which tcount > ttable (9.135 > 1.683); as a result, Ho was accepted. Thus, it can be concluded that there was a significant influence of character education on students’ learning outcomes on the theme of “Indahnya Kebersamaan” at grade IV SD Negeri 177072 Halado in the academic year 2020/2021